Design of a Drying Machine for Charcoal Bricks to Improve Cost Efficiency in Production and Profitability using the Quality Function Deployment Method - Nabil Hasabi Saputra; Handy Febri Satoto; Herlina Herlina (Telkom University, 2025)
The charcoal briquette MSME in Gedangan Subdistrict, Sidoarjo Regency, is a business engaged in the production of alternative energy based on coconut shell waste and sawdust. The production process involves burning, grinding, mixing adhesives, molding, and drying. However, based on observations, around 30% of raw materials are not optimally utilized because they become waste in the form of ash and coarse charcoal. This condition causes low production efficiency and increased operational costs. In addition, the capacity of the existing charcoal briquette drying machine is still limited, the molding results are often inconsistent, and the durability of the machine material is relatively low. This study aims to design a more efficient charcoal briquette molding machine that suits the needs of MSMEs by using the Quality Function Deployment (QFD) approach. This method focuses on translating user needs into technical product requirements, so that the machine design not only considers technical aspects but also meets user expectations. The design results are expected to increase productivity, reduce raw material waste, produce briquettes with uniform quality, and reduce production costs. With a QFD-based charcoal briquette molding machine design, Arang Briket SMEs are expected to maintain production continuity, increase competitiveness, and become an example of the application of appropriate technology in biomass-based alternative energy processing.